Efeito protetor do Nitrosil-Rutênio (Cis[Ru(bpy)2SO3NO]+(PF6) em modelos experimentais de lesões gástricas em camundongos – envolvimento da via NO/GCs/KATP - Santana, Ana Paula Macêdo (2013)
Gastric lesions associated to excessive consumption of nonsteroidal anti- inflammatory drugs (NSAIDs) and ethanol have an important role in clinical gastroenterology. The drugs with gastric antisecretory action, such as proton pump inhibitors, represent the main option in the treatment of these pathologies. Aim: To evaluate the effect of NO donor nitrosyl-ruthenium (Rut-NO) in gastric mucosal defense in experimental models of gastric damage in mice, as wellthe involvement of soluble guanylate cyclase (sGC) and KATP channels in this effect. Methods: Protocol 1-mice were pre-treated with Rut-NO (3mg/Kg, vo), ruthenium (2.3mg/Kg, p.o) or nitroprusside (SNP) at a dose of 10mg/kg, p.o, half an hour before administration by gavage of 50% ethanol. In another group, the animals were pre- treated with ODQ (10mg/kg, po) or glibenclamide (10mg/kg, ip) thirty minutes or 1 hour prior, respectively, the treatments mentioned above. After 1h, the animals were sacrificed and the stomachs removed for evaluation of gastric lesions by computerized planimetry. In addition, fragments of tissue were removed for microscopic analysis and measurement of glutathione (GSH) and malondialdehyde (MDA) levels. Protocol 2-mice were pretreated with Rut-NO (3mg/kg, po), ruthenium (2.3mg/Kg, po) or nitroprusside (10mg/kg, po) thirty minutes before administration by gavage of naproxen (NPX -300mg/Kg). In another group, the animals were pretreated with ODQ (10mg/kg, po) or glibenclamide (10mg/kg, ip) thirty minutes or 1 hour prior, respectively, the treatments mentioned above. After 6h, the animals were sacrificed and the stomachs removed for evaluation of gastric lesions using a digital caliper. Samples of gastric mucosa of these animals were removed for measurement of MPO and cytokines TNF-α and IL-1β and microscopic analysis. The adhesion of leukocytes of Rut- NO and Ruthenium groups was assessed by intravital microscopy.To study the gastric anti- secretory activity other groups of animals were treated with Rut-NO (3mg/Kg), Ruthenium (2.3mg/Kg) or omeprazole (10mg/Kg) 1 h before the pylorus ligation surgery, 4h later the animals were sacrificed, the stomachs were removed and gastric juice collected in order to verify the volume and acidity, an aliquot of gastric juice of Rut-NO and ruthenium groups were colected for nitrite determination. Results: In the model of gastropathy induced by ethanol administration Rut-NO or SNP, but not the ruthenium group, prevented the gastric injury. This protection was accompanied by an increase of GSH and decreased levels of gastric MDA when compared to the group treated only with ethanol. ODQ (10mg/Kg) and glibenclamide (10mg/Kg) completely reversed this protective effect of Rut-NO and SNP. In the model of gastric injury induced by NPX, Rut-NO or SNP, but not the group ruthenium, prevented NPX injury by lowering the levels of MPO, TNF-α, IL-1β and neutrophil adhesion. Rut-NO did not alter the acid gastric secretion. Conclusion: Rut-NO prevented the gastric lesion, the consume of GSH and the increased lipid peroxidation induced by ethanol. Rut-NO also decreased the MPO and cytokines levels, prevented the gastric lesions and decreased neutrophil adhesion induced by NPX. The gastroprotective mechanism of action of nitros ruthenium is dependent of the NO/sGC/KATP pathway. Nitrosyl-ruthenium showed a gastroprotective activity similar to the standard NO donor sodium nitroprusside.